Analysis of Menopausal Women’s Perception Toward Signs and Symptoms of Menopause - Diah Retno Utami; Santi Wahyuni (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Menopausal women experience physical and hormonal changes so that it often causes problems. This study is generally to identify menopausal women’s perception toward signs and symptoms of menopause in Kalijaga which is claimed as the village with the highest number of menopausal women in Cirebon. This study used descriptive quantitative research by applying the cross-sectional approach. The population of this study was women aged 45-55 years which were chosen using purposive sampling technique. Menopause Rating Scale (MRS) was used as the instrument of the study. The data were analyzed using descriptive analysis. The findings showed that there were some signs and symptoms experienced by the respondents namely hot flushes and sweating (90.7%), heart discomfort (46.4%), sleep problems (72.2%), depressive mood (70.1%), irritability (76.3%), anxiety (75.3%), physical and mental exhaustion (80.4%), sexual problems (58.8%), bladder problems (71.1%), vaginal dryness (74.2%), joint and muscular discomfort (89.7%). The symptoms had different levels of severity and include all three dimensions. In addition, Most of the respondents had negative perceptions toward the signs and symptoms of menopause. Based on the result of the study, it can be concluded that the respondents experience eleven signs and symptoms of menopause at varying scales of severity. It is suggested for the respondents to recognize the signs and symptoms of menopause and utilize health services in order to address the problems due to the signs and symptoms of menopause. It is also recommended for the respondents to follow elderly health programs.Keywords: Menopause, Perception, Signs, and Symptoms